Increasing Knowledge of Diabetes Mellitus Patients through Dietary Assistance at the Gurah Community Health Center, Kediri, East Java - Nurwijayanti; Sad Omega Kencanawaty; Lasito (Universitas STRADA Indonesia, 2025)
Considering the high prevalence of Diabetes Mellitus in Indonesia, education on proper eating patterns is important to control blood sugar and prevent serious impacts for patients. This report aims to increase the knowledge of Gurah Public Health Center prolanis patients about the importance of diet in preventing complications of Diabetes Mellitus. The method of implementing community service activities is carried out using lecture and discussion methods, using leaflets and presentations. Patients receive an explanation about Diabetes Mellitus, appropriate eating patterns, and the principles of balanced nutrition. This activity includes a pre-test and post-test to measure the increase in participants' knowledge. The result of the activity was that there was a significant increase in participants' understanding, shown by the average post-test results which were higher than the pre-test, indicating educational success. Conclusions and suggestions from community service are because this program has succeeded in increasing knowledge about the management of Diabetes Mellitus among patients. It is recommended that similar activities be carried out on an ongoing basis to strengthen public awareness and understanding of the prevention and management of Diabetes Mellitus.